2012
DOI: 10.1371/journal.pone.0034730
|View full text |Cite
|
Sign up to set email alerts
|

Resident Cardiac Immune Cells and Expression of the Ectonucleotidase Enzymes CD39 and CD73 after Ischemic Injury

Abstract: BackgroundThe ectoenzymes CD39 and CD73 are expressed by a broad range of immune cells and promote the extracellular degradation of nucleotides to anti-inflammatory adenosine. This study explored the abundance of CD73 and CD39 on circulating and resident cardiac leukocytes and coronary endothelial cells under control conditions and in response to inflammation following myocardial ischemia and reperfusion (I/R).Methods and ResultsA method was elaborated to permit FACS analysis of non-myocardial cells (resident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 44 publications
(60 reference statements)
8
75
0
1
Order By: Relevance
“…1C). These results are in full agreement with a recent finding that human RBC do not express detectable levels of the ecto-ATPase CD39/NTPDase2 (18). Therefore, ARL 67156 was not used in any subsequent experiments.…”
Section: Rbc Cr1 Ligation Promotes Atp Release-ligation Of Rbcsupporting
confidence: 91%
“…1C). These results are in full agreement with a recent finding that human RBC do not express detectable levels of the ecto-ATPase CD39/NTPDase2 (18). Therefore, ARL 67156 was not used in any subsequent experiments.…”
Section: Rbc Cr1 Ligation Promotes Atp Release-ligation Of Rbcsupporting
confidence: 91%
“…Recent studies indicated that the murine myocardium harbors abundant tissueresident macrophages and bona fide dendritic cells in the steady state (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). In the present study, we observed that a small population of B and T lymphocytes can also be consistently found in the myocardial parenchyma of healthy mice.…”
Section: Discussionsupporting
confidence: 72%
“…myocardial | aging | T cells | inflammation | inflammaging T he myocardial cellular composition has been revisited in recent years, and leukocyte subsets residing in the healthy heart have been described (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Cardiac-resident macrophages exhibiting an M2-like gene expression profile were found to be distributed in close association with the coronary vascular bed (3), and niches for dendritic cells (CD11c + MHC-II high CD80/86 low ) were found near the cardiac valves of the intact heart (1).…”
mentioning
confidence: 99%
“…Postinfection, the influx of immune cells consumes large quantities of oxygen, and ischemic cells rapidly respond to the hypoxic and inflammatory environment by releasing ATP (normally present within cardiomyocytes in millimolar concentrations) (13,14). Once released, the ATP is converted to ADP/AMP and then to ADO by the ectonucleoside triphosphate diphosphohydrolase-1 (CD39) and the ecto-5'-nucleotidase (CD73), respectively.…”
Section: Hagas Disease Is Caused Bymentioning
confidence: 99%